Anti-colon cancer activity of amino acid ester betulinates: Apoptosis induction and IL1B gene expression in PBMCs by the lead compound - Lyuba Miteva; Antonia Grigorova; Neli Dimitrova; Boncho Grigorov; Ani Georgieva; Paula Ossowicz-Rupniewska; Joanna Klebeko; Maya Guncheva (Pensoft Publishers, 2024)
Betulinic acid (BA) is a natural pentacyclic triterpenoid with significant pharmaceutical potential. We found that converting BA into amino acid ethyl ester salts alters its cytotoxic effect on colorectal adenocarcinoma cells (HT-29). Among these salts, the estimated half-maximal inhibitory concentration (IC50) at 72 h varies by up to fifteenfold. The proline ethyl ester [ProOEt] salt, the most active compound, exhibited an IC50 value of 3.8 µM, which is 4.8 times lower than that of the parent BA. We observed that exposure to BA or [ProOEt][BA] induced apoptosis in HT-29 cells. Additionally, the proline-based salt led to a higher level of IL1B gene expression in PBMCs at a lower stimulation concentration.